The Preferential Concept of Pro bono Publico as a Guarantee of Legal Certainty of Copyright Waqf in the perspective of Indonesian Law - Utari Dewi Fatimah; Denny Surya Sentosa Denny; Siti Rodiah Siti Rodiah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The declarative principle in copyright protection and the constitutive principle in waqf implementation within Indonesia’s legal system have created a normative disharmony, obstructing the legal recognition of intellectual property-based waqf. This misalignment has led to the absence of a clear legal mechanism for facilitating copyright as a valid and productive waqf object. This study aims to formulate an alternative concept, Preferensial Pro Bono Publico, as an administrative framework that ensures legal certainty in the waqf of copyright without compromising the core declarative nature of copyright law. Employing a normative legal research method that combines conceptual and statutory approaches, and supported by qualitative juridical analysis of primary and secondary legal sources, the findings reveal that this concept can fill the regulatory vacuum by providing a functional administrative registration pathway for socially-driven rights transfers. The analysis indicates that the model aligns with responsive legal theory, legal functionalism, and the maqashid al-shariah framework in Islamic jurisprudence, while contributing to the advancement of progressive legal doctrine. Its broader implications include opportunities for regulatory reform, inter-agency system integration, and the strengthening of intellectual property-based philanthropy in the digital era. Thus, Preferensial Pro Bono Publico functions not only as a normative legal innovation, but also as a social instrument for the equitable redistribution of copyright benefits in a sustainable manner.